The Age as a Resource: Active Ageing in Slovenia and New EU Member States - Pušnik, Ksenja; Šlebinger, Monika; Bradač Hojnik, Barbara; Rebernik, Miroslav (University of Maribor Press, 2007)
In the monograph we provide an insight into existing and developing ageing paradigm in Europe, and try to contribute to a better understanding of the role and the perspectives of governments, social partners and the wider public with regard to the improvement of the employment situation of older workers and the extension of working life in Slovenia and selected New Member States. We are informing on the development of measures/policies of social partners and governments in the countries under consideration (e.g. related to the labour market, social protection, taxation, training, work environment) and identify and present some case studies on age management initiatives, applied at individual company or organisation level (e.g. in the field of recruitment, training, health) in the Slovenia and countries subject to investigation. Finally, by synthesising all information we draw some conclusions and provide guidance for future strategies in the field of age management in the countries analysed.